A Garden of Wandering: A Response to Simon During. - Joy, Eileen A. (Australian Humanities Review, 2015)
The article talks about precariousness in the society and the impacts on humanities due to neoliberalism as a part of a response to essay by author Simon During dealing with topics including global economics, capitalism, and Open Access (OA) movement.